Management and Counselling of Patients with Recurrent Pregnancy Loss Presenting to an Infertility Specialist – A Review Article (Journal of Comilla Medical College Teachers' Association, 2024)
Background: Recurrent pregnancy loss (RPL) is defined as the occurrence of two or more consecutive miscarriages before 20 weeks of gestation. It affects approximately 1-2 % of couples trying to conceive and be a devastating experience for those affected. The etiology of RPL is multifactorial, encompassing genetic, anatomical, hormonal, immunological and environmental factors. Genetic abnormalities, such as chromosomal rearrangement, are implicated in a significant proportion of cases. Uterine anomalies and hormonal imbalances also contribute to pregnancy loss, while autoimmune disorders and blood clotting abnormalities play a role in some cases. Diagnostic approaches involve a comprehensive evaluation including karyotyping, imaging studies and screening for autoimmune disorders. Management strategies are tailored to the underlying causes when identified and may include surgical interventions, medical therapies and lifestyle modifications. Despite advancements in understanding the causes and treatment of RPL, the condition remains a challenging area of reproductive medicine. This purpose of this review study is to address the etiology and pathology of RPL in women presenting with sub fertility and infertility in an infertility clinic which will encourage other researchers. Early detection and intervention of the factors responsible of RPL will help the patient suffering from RPL and will achieved a successful reproductive life.J Com Med Col Teachers Asso July 2024; 28(2):100-104